A decision checklist for gender-responsive plant and animal breeding - CGIAR Research Program on Roots, Tubers and Bananas (CGIAR Research Program on Roots, Tubers and Bananas, 2018)
The decision checklist is a practical tool developed by the CGIAR Gender and Breeding Initiative to help breeding programs become more gender-responsive.